(untitled) (Bibliouniversitas@ABRM.md, 2025)
The article highlights the fundamental role of the Romanian Information Center in Bălți (CIR) in preserving, promoting and consolidating the Romanian cultural and linguistic identity in the northern part of the Republic of Moldova. Structured chronologically, the material provides details about the establishment, development and activities of the Center, highlighting the support provided by Romania through projects to provide information resources and technical support. The positive impact of the CIR in promoting the Romanian language, organizing cultural events and creating an inclusive educational space is highlighted. The Center’s activity contributes to strengthening cultural ties between Romania and the Romanian communities in the Republic of Moldova, through the involvement of local and international partners, as well as through the efficient use of digital platforms for the dissemination of cultural values. The article reflects the complexity and relevance of the CIR as a promoter of Romanian identity.